Wages, Unemployment, and the Underground Economy - Ann-Sofie Kolm; Birthe Larsen (Center for Economic Studies and ifo Institute (CESifo), 2003)
While examining the macroeconomic effects of increased government control of the informal sector, this paper develops a two-sector general equilibrium model featuring matching frictions and worker-firm wage bargaining. Workers search for jobs in both the formal and the informal sector. We analyse the impact of higher punishment rates and a higher audit rate on labour market performance. We find that a higher punishment rate reduces the size of the informal sector and reduces unemployment. A higher audit rate has an ambiguous impact on unemployment, and may actually increase the size of the underground economy.
Keywords: 330; tax evasion; underground economy; matching; bargaining; unemployment